Билингвална интерференция в крайния български Северозапад - Vladislav, Marinov (Zenodo, 2008)
The book contains an introduction, two chapters and 4 attachments. The introduction deals with the definition of the object , goals , tasks and methods of the research. The object of this sociolinguistic work is the Bulgarian language situation in the endmost north-western region of Bulgaria, taking into account the results of Vlach influence. This problem is crucial and is being reviewed by Bulgarian linguistics for the first time. The idiolect material was gathered from five villages in the Municipality of Bregovo.The sociolinguistic methods were the most appropriate to follow, because the local residents are bilingual, i.e. in an unofficial environment they use formations of more than one language (in this particular case – Bulgarian language and Vlach dialect). The language situation (LS) in a particular area is a result of the interaction between the subsystems of one language or several language formations. The monolingual LS consists of an a-norm (an urban colloquial literary norm); b-norm (urbanized territorial dialects called mesolects) and c-norm (territorial dialects that have been only slightly urbanized). In terms of Bulgarian speech used by the residents of the Municipality of Bregovo, the a-norm is a colloquial literary norm with a few Vlach elements , the b-norm is a West Bulgarian mesolectic norm with Vlach elements and the c-norm is an everyday life colloquial norm with significant number of Vlach elements . All three components of the Bulgarian colloquial speech in the endmost north-western region are influenced by the Vlach dialectand could be distinguished by their degree of interference .